QTL mapping and candidate gene analysis of element accumulation in rice grains via genome-wide association study and population genetic analysis - Min Li; Mengxue Gao; Jinmei Huang; Shaojuan Jin; Yamei Lv; Lin Wang; Tao Huang; Fengcai Wu; Zhijian Xu; Yinghua Pan; Zhixia Liu; Chaopu Zhang; et al. (BMC Plant Biology)
Abstract Background Toxic heavy metal elements in soils are major global environmental issues and easily migrate to crop grains to cause severe problems in human health, whereas moderately essential elements such as selenium are beneficial for human health. The accumulation of heavy metals and essential elements in rice grains and their genetic mechanisms are still poorly understood. Results We conducted genetic dissection of four toxic heavy metal elements (lead, cadmium, mercury, and chromium), one quasi metallic element (arsenic), and one essential element (selenium) in grains of 290 Xian and 308 Geng rice accessions through a genome-wide association study (GWAS) based on three statistical models and assays of element concentrations from three environments. A total of 99 quantitative trait loci (QTLs) were identified. Among these QTLs, 18.2% overlapped between/among two or more elements, indicating that some QTLs related to the accumulation of certain elements may depend on other heavy metal elements or be involved in the collaborative transport of other elements. Moreover, at least 14 QTLs/regions were identified in the same regions, containing 12 cloned genes reported to be associated with element accumulation or tolerance-related traits, while the remaining 85 were new QTLs. A total of 62 promising candidate genes were identified from 50 major QTLs, of which 25 genes were newly discovered in this study. More importantly, population genetic analysis revealed 26 and 15 intraspecies divergent regions affecting element concentrations in the Xian and Geng subspecies, respectively, including 25 QTLs identified in this study and 13 previously reported and cloned genes. Conclusions Our findings will facilitate further gene cloning and dissection of the genetic mechanisms of element accumulation in rice grains to improve grain quality.